2009
DOI: 10.1038/mt.2009.157
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Mesenchymal Stem Cells for Treatment of Experimental Autoimmune Encephalomyelitis

Abstract: The use of allogeneic "universal donor" mesenchymal stromal cells (MSCs) may be a substantial clinical convenience for treatment of autoimmune ailments such as multiple sclerosis. We therefore tested whether allogeneic MSCs can be exploited for treatment of experimental autoimmune encephalomyelitis (EAE) in mice with otherwise intact immune system. Administration of allogeneic Balb/c-derived MSCs to C57Bl/6 mice with pre-established EAE led to a significant decrease in disease score over time comparable to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
88
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 19 publications
(22 reference statements)
7
88
0
4
Order By: Relevance
“…However, the immune modulatory function of BM-MSCs has been documented in graftversus-host disease [4][5][6], autoimmune encephalomyelitis [17], sepsis [3], collagen-induced arthritis, and bowel inflammation [15,16,20]. But whether other SC categories have the ability to exert comparable effects was unknown and our results provide novel information supporting the view that a variety of SCs share the critical aspect of being immune privileged.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…However, the immune modulatory function of BM-MSCs has been documented in graftversus-host disease [4][5][6], autoimmune encephalomyelitis [17], sepsis [3], collagen-induced arthritis, and bowel inflammation [15,16,20]. But whether other SC categories have the ability to exert comparable effects was unknown and our results provide novel information supporting the view that a variety of SCs share the critical aspect of being immune privileged.…”
mentioning
confidence: 54%
“…Several SC subtypes, including neural SCs [10] and mesenchymal stromal cells (MSCs) [11][12][13][14], possess regenerative potential and may interact with immune effector cells (IECs), profoundly influencing their function in vitro and in vivo. The immune system plays a critical role in the pathogenesis and progression of a number of degenerative diseases, raising the possibility that SCs may be effective in repairing the damaged organ by promoting cell formation and modulating the associated immune response [6,[14][15][16][17][18][19][20]. Based on this premise, the immunogenicity and immune modulatory properties of SCs have to be carefully characterized to decipher their potential clinical import.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow stromal cells (BMSCs) have recently been shown to suppress harmful immune responses in patients with acute graftversus-host disease (4,5) and in several animal models of allogeneic rejection (6)(7)(8), a variety of autoimmune diseases (9)(10)(11), and lung injury (12)(13)(14)(15). The authors of many of these studies concluded that BMSC-driven immunosuppression results from a shift in Th1/Th2 balance (8,16,17).…”
mentioning
confidence: 99%
“…There are several reports regarding the beneficial roles of the immunomodulatory effects of different adult SC types, mainly MSCs, in different disease models such as graft-versus-host disease [33], experimental autoimmune encephalomyelitis [34], inflammatory bowel disease [35], and systemic lupus erythematosus [36]. The safety and efficacy of MSC treatments have been validated in clinical trials [37][38][39][40] and many others are currently in progress.…”
Section: Discussionmentioning
confidence: 99%